Daily energy expenditure during lactation is strongly selected in a free‐living mammal. (21st July 2014) - Fletcher, Quinn E.; Speakman, John R.; Boutin, Stan; Lane, Jeffrey E.; McAdam, Andrew G.; Gorrell, Jamieson C.; Coltman, David W.; Humphries, Murray M.
Summary: Energy expenditure is a trait of central importance in ecological and evolutionary theory. We examined the correlates of, the strength of selection on, and the heritability of, daily energy expenditure (DEE; kJ day −1 ) during lactation in free‐ranging North American red squirrels ( Tamiasciurus hudsonicus ). Over 7 years, lactating squirrels with greater DEE had higher annual reproductive success (ARS; standardized selection gradient: β′ = 0·47; top 12% of published estimates). Surprisingly, positive fecundity selection on lactation DEE for increased ARS did not result because lactation DEE was correlated with typical measures of reproductive performance and/or investment. We found no evidence of costs of elevated lactation DEE acting through female survival, subsequent year lactation DEE or subsequent year reproduction. Lactation DEE was not significantly repeatable, and heritability was not significantly different from zero. Elevated lactation DEE enhances ARS through a link between DEE and an unidentified measure of maternal or environmental quality, but there is limited evolutionary potential for lactation DEE to respond to our documented selection. Abstract : Lay Summary